Drawing the Greek vase - Meyer, Hans-Caspar; Petsalē-Diomēdē, Alexia (Visual conversations in art and archaeology, 2023)
How have two-dimensional images of ancient Greek vases shaped modern perceptions of these artefacts and of the classical past? This is a scholarly volume devoted to the exploration of drawings, prints, and photographs of Greek vases in modernity, and traces the ways artists have depicted Greek vases in a range of styles and contexts.